Spatial Cognition and the Semantics of Prepositions in English, Polish and Russian - Cienki, Alan J. (Slavistische Beitraege, 1989)
The object of this work will be a selected group of prepositions in English, Polish and Russian which can express spatial relationships? This study focuses on "everyday" usage of the languages in question.